A preparation method for sewage oxidation treatment material based on magnetocaloric effect
By forming an oxidized trimethylamine iron organic compound layer on the surface of the foamed copper matrix and loading manganese magnesium gadolinium oxide nanocrystals, the materials are treated with magnetothermal effect, the difficult degradation of 2,2',5,5'-tetrachloride in the prior art is solved by treating the material with a magnetothermal effect. The problem of benzine wastewater has achieved efficient degradation effect and treatment stability.
Patent Information
- Application Number
- CN202411165187.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The prior art cannot effectively degrade and treat organic wastewater containing 2,2',5,5'-tetrachlorobenzidine. The physical treatment method only transfers rather than decomposes. The chemical oxidation degradation effect is not ideal, and there is a risk of secondary pollution.
Using the preparation method of wastewater oxidation treatment material based on magnetothermal effect, the oxidized trimethylamine iron organic compound layer is formed on the surface of the foam copper matrix and loaded with manganese magnesium gadolinium oxide nanocrystals, and the alternating magnetic field is used to promote 2,2',5,5. '-Degradation of tetrachlorobenzidine.
The degradation rate of 2,2',5,5'-tetrachlorobenzidine is significantly improved, and the reuse stability of the treated materials is maintained, reducing the risk of secondary pollution during sewage treatment.
Smart Images

Figure CN118894589B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic sewage treatment, in particular to a method for preparing sewage oxidation treatment materials based on magnetocaloric effect. Background Art
[0002] Benzidine yellow organic pigment has excellent coloring properties, bright colors, outstanding solvent resistance and heat resistance, and is widely used in the fields of coatings, plastics and printing. The synthesis method of benzidine yellow organic pigment is coupling after diazotization. Since the diazotized component in the intermediate process of its synthesis is 2,2',5,5'-tetrachlorobenzidine, the synthesis process of benzidine yellow organic pigment will produce a large amount of organic wastewater containing 2,2',5,5'-tetrachlorobenzidine. 2,2',5,5'-tetrachlorobenzidine is an organic substance in which the 2,2',5,5' position of benzidine is substituted by chlorine. It has high chemical stability and carcinogenic toxicity, is easy to enrich, and is difficult to degrade and control, posing a serious threat to the earth's ecological environment.
[0003] The current treatment technologies for organic wastewater containing 2,2',5,5'-tetrachlorobenzidine include physical treatment processes such as adsorption and membrane exchange adsorption, as well as chemical processes of oxidative decomposition. Physical treatment processes such as adsorption and membrane treatment only transfer 2,2',5,5'-tetrachlorobenzidine, but do not decompose it into harmless substances, which will cause secondary pollution. At the same time, the effect of oxidative degradation chemical processes in treating organic wastewater containing 2,2',5,5'-tetrachlorobenzidine is not ideal at present.
[0004] The alternating magnetic field can cause superparamagnetic materials to produce a significant magnetocaloric effect, which can significantly promote the kinetic rate of chemical reactions. The present invention combines the magnetocaloric effect of superparamagnetic materials with the oxidative degradation chemical reaction process of 2,2',5,5'-tetrachlorobenzidine, which has an important role in promoting the 2,2',5,5'-tetrachlorobenzidine organic wastewater treatment technology. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a sewage oxidation treatment material based on the magnetocaloric effect. The oxidation treatment material prepared by the method has an excellent 2,2',5,5'-tetrachlorobenzidine degradation rate and excellent repeated use stability.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a sewage oxidation treatment material based on magnetocaloric effect, comprising the following steps performed in sequence:
[0008] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 Organic compound layer;
[0009] Step [2] converts the trimethylamine oxide iron Fe(C3H9NO) organic compound layer into a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer through the substitution of the maleimide group C4H3NO2; 3 The organic compound layer is converted into a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer;
[0010] Step [3] loads manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals on the maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer to obtain the sewage oxidation treatment material.
[0011] Preferably, step [1] specifically includes the following operations:
[0012] a1. Add carbonyl iron powder, ferric chloride, diethylamine and acetic acid to deionized water and mix to form a base solution; add methyl formate to methanol and mix to form an additive solution; add a certain amount of the additive solution to the base solution and mix to form a synthesis solution;
[0013] a2. Immerse the copper foam sample in the synthesis solution, heat to 60 - 90 °C, and react for 4 - 6 hours to obtain copper foam with a trimethylamine oxide iron Fe(C3H9NO) organic compound layer formed on the surface, denoted as intermediate A. 3 The copper foam with a trimethylamine oxide iron Fe(C3H9NO) organic compound layer formed on the surface is denoted as intermediate A.
[0014] Preferably, in step a1, the concentration of carbonyl iron powder in the base solution is 160 g / L - 220 g / L, the concentration of ferric chloride is 50 g / L - 90 g / L, the concentration of diethylamine is 90 mL / L - 160 mL / L, and the concentration of acetic acid is 90 mL / L - 140 mL / L; the concentration of methyl formate in the additive solution is 110 mL / L - 130 mL / L; the volume ratio of the additive solution to the base solution in the synthesis solution is 1 - 3:3 - 5.
[0015] Preferably, in step a2, the weight of the copper foam immersed in each liter of the synthesis solution is 260 - 290 g.
[0016] Preferably, step [2] specifically includes the following operations:
[0017] b1. Add N - methylaniline and phenylhydrazine to ethanol and mix to form a first intermediate solution; add glyoxal and potassium permanganate to deionized water and mix to form a second intermediate solution; add a certain amount of the second intermediate solution to the first intermediate solution and mix to form a substitution solution;
[0018] b2. The intermediate A is immersed in the replacement solution and reacted at room temperature for 1.5-3 hours to obtain a copper foam having a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer formed on the surface, which is recorded as intermediate B.
[0019] Preferably, in step b1, the concentration of N-methylaniline in the first intermediate solution is 160 mL / L-190 mL / L, and the concentration of phenylhydrazine is 210 mL / L-240 mL / L; the concentration of glyoxal in the second intermediate solution is 150 g / L-210 g / L, and the concentration of potassium permanganate is 40 g / L-70 g / L; and the volume ratio between the first intermediate solution and the second intermediate solution in the replacement solution is 3~7:1~2.
[0020] Preferably, in step b2, the weight of the intermediate A immersed in each liter of the replacement liquid is 270-310 g.
[0021] Preferably, the step [3] specifically includes the following operations:
[0022] c1. Magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxysuccinic acid are added to deionized water to form an intermediate product forming liquid, intermediate B is immersed in the intermediate product forming liquid, placed in a microwave reactor, and microwave heated to 90°C-140°C at a rate of 10-30°C / min, and reacted for 0.5-2 hours to load manganese magnesium gadolinium oxide intermediate product on the maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer on the surface of the foam copper substrate, and finally obtain intermediate C;
[0023] c2. placing the intermediate C into a low temperature box furnace and keeping it at 150°C-300°C for 3-5 hours to convert the manganese magnesium gadolinium oxide intermediate into manganese magnesium gadolinium oxide nanocrystals, and finally obtaining the wastewater oxidation treatment material.
[0024] Preferably, the magnesium chloride concentration of the intermediate product forming liquid in step c1 is 40 g / L-60 g / L, the manganese nitrate concentration is 120 g / L-170 g / L, the gadolinium nitrate concentration is 230 g / L-270 g / L, the allyl alcohol concentration is 60 mL / L-90 mL / L, and the 2-hydroxysuccinic acid concentration is 110 g / L-150 g / L.
[0025] Preferably, in step c1, the weight of the intermediate B immersed in each liter of the intermediate product forming liquid is 220-270 g.
[0026] Positive effects of the present invention: The sewage oxidation treatment material (copper foam-based maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic matter-loaded manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals) prepared by the method according to the present invention have the following structural characteristics: The Fe(C4H3NO2)2(C3H9NO) structure is a planar triangular structure of Fe(C4H3NO2)2(C3H9NO) organic compound formed by taking iron ions as the central ions and trimethylamine oxide C3H9NO and maleimide C4H3NO2 (the structure is as Figure 3 shown), the iron ions are located at the centroid of the planar triangle, and the trimethylamine oxide C3H9NO and maleimide C4H3NO2 ligands are located at the vertices of the planar triangle; Mn 1-x Mg x Gd2O4(0<x≤0.3) nanocrystals have a spinel structure (the structure is as Figure 4 shown), the oxygen ions are arranged in a cubic close-packed manner, the gadolinium ions are located in the octahedral voids, and the manganese ions and magnesium ions are located in the tetrahedral voids. Based on the above structural characteristics, among them, maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) has superparamagnetism. Under the action of an alternating magnetic field, due to Brown relaxation and Neel relaxation, a magnetic thermal effect is generated. This magnetic thermal effect is concentrated locally and is closely related to the iron ions of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO), which can cause the temperature of the Mn 1- x Mg x Gd2O4 nanocrystals to increase significantly, oxidize the divalent manganese ions of the Mn 1-x Mg x Gd2O4 nanocrystals to form tetravalent manganese ions, and the tetravalent manganese ions undergo an electrophilic reaction with the aromatic ring of 2,2',5,5'-tetrachlorobenzidine to break, causing the degradation of 2,2',5,5'-tetrachlorobenzidine; in addition, the alternating magnetic field thermal effect of Fe(C4H3NO2)2(C3H9NO) also reduces the stability of the bonding between the atoms of 2,2',5,5'-tetrachlorobenzidine adsorbed on the copper foam-based treatment material, thereby further promoting the degradation of 2,2',5,5'-tetrachlorobenzidine.
[0027] In summary, the sewage oxidation treatment material prepared according to the present invention has excellent 2,2',5,5'-tetrachlorobenzidine degradation rate and excellent reusability stability. Brief Description of the Drawings
[0028] Figure 1 is a schematic diagram of the preparation process of the sewage oxidation treatment material described in the present invention;
[0029] Figure 2 is the structural schematic diagram of Fe(C3H9NO) of the present invention 3 ;
[0030] Figure 3 is the structural schematic diagram of Fe(C4H3NO2)2(C3H9NO) of the present invention
[0031] Figure 4 is Mn of the present invention 1-x Mg x Gd2O4(0 < x ≤ 0.3);
[0032] Figure 5a is the removal rate of 2,2',5,5'-tetrachlorobenzidine under different pH conditions when an alternating magnetic field is applied in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention
[0033] Figure 5b is the removal rate of 2,2',5,5'-tetrachlorobenzidine under different pH conditions without an applied magnetic field in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention
[0034] Figure 6a is the removal rate of 2,2',5,5'-tetrachlorobenzidine when reused for the 5th time under different pH conditions when an alternating magnetic field is applied in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention
[0035] Figure 6b is the removal rate of 2,2',5,5'-tetrachlorobenzidine when reused for the 5th time under different pH conditions without an applied magnetic field in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention Specific Embodiments
[0036] Referring to Figure 1 , the present invention provides a preparation method of a sewage oxidation treatment material based on the magnetothermal effect, comprising the following steps carried out in sequence:
[0037] Step [1] Form an organic compound layer of trimethylamine oxide iron Fe(C3H9NO) on the surface of a copper foam substrate, specifically including the following operations: 3 ;
[0038] a1. Add carbonyl iron powder, ferric chloride, diethylamine and acetic acid to deionized water and mix to form a base solution with a carbonyl iron powder concentration of 160 g / L - 220 g / L, a ferric chloride concentration of 50 g / L - 90 g / L, a diethylamine concentration of 90 mL / L - 160 mL / L, and an acetic acid concentration of 90 mL / L - 140 mL / L; add methyl formate to methanol and mix to form an additive solution with a methyl formate concentration of 110 mL / L - 130 mL / L; add the additive solution to the base solution in a volume ratio of 1 - 3:3 - 5 and mix to form a synthetic solution.
[0039] a2. Immerse a copper foam specimen in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution is 260 - 290 g), heat to 60 - 90 °C, and react for 4 - 6 hours to obtain copper foam with an organic compound layer of trimethylamine oxide iron Fe(C3H9NO) 3 (the structure is as Figure 2 shown) marked as intermediate A.
[0040] Step [2] converts the organic compound layer of trimethylamine oxide iron Fe(C3H9NO) into an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) by substitution of the maleimide group C4H3NO2, specifically including the following operations: 3 Immerse intermediate A in the substitution solution (the weight of intermediate A immersed in each liter of the substitution solution is 270 - 310 g), react at room temperature for 1.5 - 3 hours to obtain copper foam with an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) marked as intermediate B.
[0041] b1. Add N-methylaniline and phenylhydrazine to ethanol and mix to form a first intermediate solution with an N-methylaniline concentration of 160 mL / L - 190 mL / L and a phenylhydrazine concentration of 210 mL / L - 240 mL / L; add glyoxal and potassium permanganate to deionized water and mix to form a second intermediate solution with a glyoxal concentration of 150 g / L - 210 g / L and a potassium permanganate concentration of 40 g / L - 70 g / L; add the second intermediate solution to the first intermediate solution in a volume ratio of 3 - 7:1 - 2 and mix to form a substitution solution.
[0042] b2. Immerse intermediate A in the substitution solution (the weight of intermediate A immersed in each liter of the substitution solution is 270 - 310 g), react at room temperature for 1.5 - 3 hours to obtain copper foam with an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) marked as intermediate B.
[0043] Step [3] Load manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals on the organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO), specifically including the following operations:
[0044] c1. Magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxysuccinic acid are added to deionized water to form an intermediate product formation solution having a magnesium chloride concentration of 40 g / L-60 g / L, a manganese nitrate concentration of 120 g / L-170 g / L, a gadolinium nitrate concentration of 230 g / L-270 g / L, an allyl alcohol concentration of 60 mL / L-90 mL / L, and a 2-hydroxysuccinic acid concentration of 110 g / L -150 g / L, and intermediate B is immersed in the intermediate product formation solution (the weight of intermediate B immersed in each liter of the intermediate product formation solution is 220-270 g), placed in a microwave reactor, and heated at 10-30 ° C / min, microwave heating to 90°C-140°C, reacting for 0.5-2 hours, so as to load the manganese magnesium gadolinium oxide intermediate product on the maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer on the surface of the foam copper substrate, and finally obtain the intermediate C;
[0045] c2. The intermediate C is placed in a low temperature box furnace and kept at 150°C-300°C for 3-5 hours to convert the manganese magnesium gadolinium oxide intermediate into manganese magnesium gadolinium oxide nanocrystals, and finally the sewage oxidation treatment material (foam copper-based maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic matter-loaded manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals).
[0046] The preferred embodiments of the present invention are described below by way of example.
[0047] Example 1
[0048] Preferred embodiment 1 of the present invention provides a method for preparing a sewage oxidation treatment material based on magnetocaloric effect, comprising the following steps performed in sequence:
[0049] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0050] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 190 g / L, ferric chloride concentration of 70 g / L, diethylamine concentration of 150 mL / L, acetic acid concentration of 120 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 120 mL / L of the added liquid; the added liquid was added to the base liquid in a ratio of 2:5 by volume, and mixed to form a synthetic liquid;
[0051] a2. Immerse the copper foam sample in the synthetic liquid (the weight of the copper foam immersed in each liter of the synthetic liquid is 280 g), heat it to 80 °C, and react for 5 hours to obtain copper foam with a trimethylamine oxide iron Fe(C3H9NO) organic compound layer formed on its surface. 3 This is denoted as intermediate A.
[0052] In step [2], the trimethylamine oxide iron Fe(C3H9NO) organic compound layer is converted to a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer by the substitution of the maleimide group C4H3NO2. The specific operations are as follows: 3 This specifically includes the following operations:
[0053] b1. Add N-methylaniline and phenylhydrazine to ethanol to form a first intermediate liquid with an N-methylaniline concentration of 180 mL / L and a phenylhydrazine concentration of 230 mL / L. Add glyoxal and potassium permanganate to deionized water to form a second intermediate liquid with a glyoxal concentration of 200 g / L and a potassium permanganate concentration of 60 g / L. Add the second intermediate liquid to the first intermediate liquid according to a volume ratio of 5:2 between the first intermediate liquid and the second intermediate liquid to form a substitution liquid.
[0054] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 300 g), and react at room temperature for 3 hours to obtain copper foam with a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer formed on its surface. This is denoted as intermediate B.
[0055] In step [3], Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals are loaded on the maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer. The specific operations are as follows:
[0056] c1. Magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxysuccinic acid are added to deionized water to form an intermediate product formation solution with a magnesium chloride concentration of 50 g / L, a manganese nitrate concentration of 160 g / L, a gadolinium nitrate concentration of 260 g / L, an allyl alcohol concentration of 80 mL / L, and a 2-hydroxysuccinic acid concentration of 140 g / L, and intermediate B is immersed in the intermediate product formation solution (the weight of intermediate B immersed in each liter of the intermediate product formation solution is 260 g), placed in a microwave reactor, and heated to 130° C. at a rate of 25° C. / min by microwaves, reacted for 1.5 hours, so as to load manganese magnesium gadolinium oxide intermediate products on the maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer on the surface of the foam copper substrate, and finally obtain intermediate C;
[0057] c2. The intermediate C is placed in a low temperature box furnace and kept at 260°C for 4 hours to convert the manganese magnesium gadolinium oxide intermediate product into manganese magnesium gadolinium oxide nanocrystals, and finally the sewage oxidation treatment material (foam copper-based maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic matter-loaded manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals), recorded as Example 1.
[0058] Comparative Example 1
[0059] This comparative example 1 provides a method for preparing a sewage treatment material, comprising the following steps performed in sequence:
[0060] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0061] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 170 g / L, ferric chloride concentration of 60 g / L, diethylamine concentration of 100 mL / L, acetic acid concentration of 100 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 115 mL / L of the added liquid; the added liquid was added to the base liquid in a ratio of 1:3 by volume to form a synthetic liquid;
[0062] a2. The copper foam sample was immersed in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution was 270 g), heated to 70 ° C, and reacted for 5 hours to obtain trimethylamine iron oxide Fe (C3H9NO) formed on the surface. 3 The foam copper of the organic compound layer is recorded as intermediate A.
[0063] Step [2] Oxidation of trimethylamine iron Fe(C3H9NO) by substitution of maleimide group C4H3NO2 3 The organic compound layer is converted into a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer, specifically including the following operations:
[0064] b1. N-methylaniline and phenylhydrazine were added to ethanol to form a mixture of N-methylaniline concentration of 180 mL / L, phenylhydrazine concentration of 220mL / L of the first intermediate solution; glyoxal and potassium permanganate were added to deionized water to form a mixture of glyoxal concentration of 160g / L, potassium permanganate concentration of 50g / L of the second intermediate solution; according to the volume ratio of the first intermediate solution to the second intermediate solution of 3: 2 ratio of the second intermediate solution was added to the first intermediate solution, mixed to form a substitute solution;
[0065] b2. The intermediate A was immersed in the replacement solution (the weight of the intermediate A immersed in each liter of the replacement solution was 280 g), and reacted at room temperature for 2 hours to obtain a foam copper having a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer formed on the surface, which was recorded as Comparative Example 1.
[0066] Comparative Example 2
[0067] This comparative example 2 provides a method for preparing a sewage treatment material, comprising the following steps performed in sequence:
[0068] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0069] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 200 g / L, ferric chloride concentration of 60 g / L, diethylamine concentration of 140 mL / L, acetic acid concentration of 130 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 120 mL / L of the added liquid; the added liquid was added to the base liquid in a ratio of 3:5 by volume, and mixed to form a synthetic liquid;
[0070] a2. The copper foam sample was immersed in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution was 280 g), heated to 80 ° C, and reacted for 5 hours to obtain trimethylamine iron oxide Fe (C3H9NO) formed on the surface. 3 The foam copper of the organic compound layer is recorded as intermediate A.
[0071] Step [2] Oxidation of trimethylamine iron Fe(C3H9NO) 3Manganese-magnesium-gadolinium oxide Mn supported on an organic compound layer 1- x Mg x Gd₂O₄ (0 < x ≤ 0.3) nanocrystals, specifically including the following operations:
[0072] c1. Add magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol, and 2-hydroxybutanedioic acid to deionized water to form an intermediate product formation solution with a magnesium chloride concentration of 50 g / L, a manganese nitrate concentration of 150 g / L, a gadolinium nitrate concentration of 252 g / L, an allyl alcohol concentration of 80 mL / L, and a 2-hydroxybutanedioic acid concentration of 130 g / L. Immerse intermediate A in the intermediate product formation solution (the weight of intermediate A immersed in each liter of the intermediate product formation solution is 260 g), place it in a microwave reactor, and microwave heat it to 130 °C at a rate of 20 °C / min for 1.5 hours to obtain an iron trimethylamine oxide Fe(C₃H₉NO) on the surface of the copper foam substrate 3 An intermediate product of manganese-magnesium-gadolinium oxide supported on an organic compound layer, and finally obtain intermediate D;
[0073] c2. Place intermediate D in a low-temperature box furnace and keep it at 200 °C for 4 hours to convert the manganese-magnesium-gadolinium oxide intermediate product into manganese-magnesium-gadolinium oxide nanocrystals, and finally obtain the sewage treatment material (copper foam-based iron trimethylamine oxide Fe(C₃H₉NO) 3 Organic matter-supported manganese-magnesium-gadolinium oxide Mn 1-x Mg x Gd₂O₄ nanocrystals), denoted as Comparative Example 2.
[0074] To analyze the degradation performance of Example 1, Comparative Example 1, and Comparative Example 2 in treating sewage containing 2,2',5,5'-tetrachlorobenzidine, use deionized water to prepare a solution with a 2,2',5,5'-tetrachlorobenzidine concentration of 40 mg / L as simulated sewage. Adjust the pH value of the above-prepared simulated sewage with hydrochloric acid and sodium hydroxide to obtain simulated sewage with pH values of 4, 5, 6, 7, and 8 respectively. Place 40 g of the sewage treatment material (i.e., Example 1, Comparative Example 1, Comparative Example 2) in each liter of the simulated sewage for 2,2',5,5'-tetrachlorobenzidine degradation treatment. The treatment time is 40 min, and the treatment conditions are an alternating magnetic field with an external frequency of 500 kHz and a magnetic field strength of 0.05 T and no external magnetic field (0 T). Use a high-performance liquid chromatograph to measure the concentration of 2,2',5,5'-tetrachlorobenzidine in the corresponding simulated sewage after the degradation treatment, and calculate the corresponding 2,2',5,5'-tetrachlorobenzidine degradation rate. The results are as follows Figure 5aIn addition, in order to compare and analyze the repeated use stability of Example 1, Comparative Example 1 and Comparative Example 2, the degradation rate of 2,2',5,5'-tetrachlorobenzidine in the corresponding simulated sewage when Example 1, Comparative Example 1 and Comparative Example 2 were reused for the fifth time under the same conditions was studied. The results are shown in FIG. Figure 6a -b as shown.
[0075] It can be seen from the experimental results that under the action of the alternating magnetic field, the magnetocaloric effect can promote the degradation of 2,2',5,5'-tetrachlorobenzidine in Example 1. Compared with the condition without the alternating magnetic field thermal effect, the degradation performance of the alternating magnetic field thermal effect oxidation treatment of 2,2',5,5'-tetrachlorobenzidine-containing wastewater is significantly improved; in contrast, the degradation performance of 2,2',5,5'-tetrachlorobenzidine wastewater in Comparative Examples 1 and 2 is not ideal whether under the condition with or without the alternating magnetic field. In addition, when Example 1 is used for the fifth time, the 2,2',5,5'-tetrachlorobenzidine under the alternating magnetic field thermal effect oxidation treatment condition can still be degraded by more than 83%, while the degradation rate of 2,2',5,5'-tetrachlorobenzidine in Comparative Examples 1 and 2 is significantly reduced when they are used for the fifth time.
[0076] In summary, the sewage oxidation treatment material prepared according to the present invention has excellent 2,2',5,5'-tetrachlorobenzidine degradation rate and excellent repeated use stability.
[0077] To illustrate in further detail, three additional examples are provided below.
[0078] Example 2
[0079] Preferred embodiment 2 of the present invention provides a method for preparing a sewage oxidation treatment material based on magnetocaloric effect, comprising the following steps performed in sequence:
[0080] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0081] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 160 g / L, ferric chloride concentration of 50 g / L, diethylamine concentration of 90 mL / L, acetic acid concentration of 90 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 130 mL / L of the added liquid; the added liquid was added to the base liquid in a ratio of 1:3 by volume to form a synthetic liquid;
[0082] a2. Immerse the copper foam sample in the synthetic liquid (the weight of the copper foam immersed in each liter of the synthetic liquid is 260 g), heat it to 60 °C, and react for 6 hours to obtain copper foam with an organic compound layer of trimethylamine oxide iron Fe(C3H9NO) formed on its surface. 3 This is designated as intermediate A.
[0083] In step [2], the organic compound layer of trimethylamine oxide iron Fe(C3H9NO) is converted into an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) through the substitution of the maleimide group C4H3NO2. The specific operations are as follows: 3 This specifically includes the following operations:
[0084] b1. Add N-methylaniline and phenylhydrazine to ethanol to form a first intermediate liquid with an N-methylaniline concentration of 190 mL / L and a phenylhydrazine concentration of 210 mL / L. Add glyoxal and potassium permanganate to deionized water to form a second intermediate liquid with a glyoxal concentration of 210 g / L and a potassium permanganate concentration of 40 g / L. Add the second intermediate liquid to the first intermediate liquid according to a volume ratio of 7:2 between the first intermediate liquid and the second intermediate liquid to form a substitution liquid.
[0085] b2. Immerse intermediate A in the substitution liquid (the weight of intermediate A immersed in each liter of the substitution liquid is 270 g), and react at room temperature for 1.5 hours to obtain copper foam with an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) formed on its surface. This is designated as intermediate B.
[0086] In step [3], manganese-magnesium-gadolinium oxide Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals are loaded on the organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO). The specific operations are as follows:
[0087] c1. Magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxysuccinic acid are added to deionized water to form an intermediate product formation solution with a magnesium chloride concentration of 40 g / L, a manganese nitrate concentration of 120 g / L, a gadolinium nitrate concentration of 270 g / L, an allyl alcohol concentration of 60 mL / L, and a 2-hydroxysuccinic acid concentration of 150 g / L, and intermediate B is immersed in the intermediate product formation solution (the weight of intermediate B immersed in each liter of the intermediate product formation solution is 220 g), placed in a microwave reactor, and heated to 90° C. at a rate of 10° C. / min by microwaves, reacted for 2 hours, so as to load manganese magnesium gadolinium oxide intermediate products on the maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer on the surface of the foam copper substrate, and finally obtain intermediate C;
[0088] c2. The intermediate C is placed in a low temperature box furnace and kept at 300°C for 3 hours to convert the manganese magnesium gadolinium oxide intermediate product into manganese magnesium gadolinium oxide nanocrystals, and finally the sewage oxidation treatment material (foam copper-based maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic matter-loaded manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals).
[0089] Example 3
[0090] Preferred embodiment 3 of the present invention provides a method for preparing a sewage oxidation treatment material based on magnetocaloric effect, comprising the following steps performed in sequence:
[0091] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0092] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 220 g / L, ferric chloride concentration of 90 g / L, diethylamine concentration of 160 mL / L, acetic acid concentration of 140 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 110 mL / L of the added liquid; the added liquid was added to the base liquid in a ratio of 3:5 by volume to form a synthetic liquid;
[0093] a2. The copper foam sample was immersed in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution was 290 g), heated to 90 ° C, and reacted for 4 hours to obtain trimethylamine iron oxide Fe (C3H9NO) formed on the surface. 3 The foam copper of the organic compound layer is recorded as intermediate A.
[0094] Step [2] converts the trimethylamine oxide iron Fe(C3H9NO) organic compound layer into a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer by substituting the maleimide group C4H3NO2, specifically including the following operations: 3 The organic compound layer is converted into a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer, specifically including the following operations:
[0095] b1. Add N-methylaniline and phenylhydrazine to ethanol to form a first intermediate solution with an N-methylaniline concentration of 160 mL / L and a phenylhydrazine concentration of 240 mL / L; add glyoxal and potassium permanganate to deionized water to form a second intermediate solution with a glyoxal concentration of 150 g / L and a potassium permanganate concentration of 70 g / L; add the second intermediate solution to the first intermediate solution according to a volume ratio of 3:1 between the first intermediate solution and the second intermediate solution to form a substitution solution;
[0096] b2. Immerse intermediate A in the substitution solution (the weight of intermediate A immersed in each liter of the substitution solution is 310 g), react at room temperature for 3 hours to obtain copper foam with a maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer formed on the surface, denoted as intermediate B.
[0097] Step [3] Loads manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals on the maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer, specifically including the following operations:
[0098] c1. Add magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol, and 2-hydroxybutanedioic acid to deionized water to form an intermediate product forming solution with a magnesium chloride concentration of 60 g / L, a manganese nitrate concentration of 170 g / L, a gadolinium nitrate concentration of 230 g / L, an allyl alcohol concentration of 90 mL / L, and a 2-hydroxybutanedioic acid concentration of 110 g / L. Immerse intermediate B in the intermediate product forming solution (the weight of intermediate B immersed in each liter of the intermediate product forming solution is 270 g), place it in a microwave reactor, and microwave heat it to 140 °C at a rate of 30 °C / min and react for 0.5 hours to load the manganese magnesium gadolinium oxide intermediate product on the maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic compound layer on the copper foam matrix, and finally obtain intermediate C;
[0099] c2. The intermediate C is placed in a low temperature box furnace and kept at 150°C for 5 hours to convert the manganese magnesium gadolinium oxide intermediate product into manganese magnesium gadolinium oxide nanocrystals, and finally the sewage oxidation treatment material (foam copper-based maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic matter-loaded manganese magnesium gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals).
[0100] Example 4
[0101] Preferred embodiment 4 of the present invention provides a method for preparing a sewage oxidation treatment material based on magnetocaloric effect, comprising the following steps performed in sequence:
[0102] Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer specifically includes the following operations:
[0103] a1. Carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water to form a carbonyl iron powder concentration of 190 g / L, ferric chloride concentration of 70 g / L, diethylamine concentration of 126 mL / L, acetic acid concentration of 115 mL / L base liquid; methyl formate was added to methanol to form a methyl formate concentration of 120 mL / L of the added liquid; the added liquid was added to the base liquid in a volume ratio of 2:4, and mixed to form a synthetic liquid;
[0104] a2. The copper foam sample was immersed in the synthetic solution (the weight of the copper foam immersed in each liter of the synthetic solution was 275 g), heated to 69 ° C, and reacted for 5 hours to obtain trimethylamine iron oxide Fe (C3H9NO) formed on the surface. 3 The foam copper of the organic compound layer is recorded as intermediate A.
[0105] Step [2] Oxidation of trimethylamine iron Fe(C3H9NO) by substitution of maleimide group C4H3NO2 3 The organic compound layer is converted into a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer, specifically including the following operations:
[0106] b1. N-methylaniline and phenylhydrazine were added to ethanol to form a mixture of N-methylaniline concentration of 175mL / L, phenylhydrazine concentration of 225mL / L of the first intermediate solution; glyoxal and potassium permanganate were added to deionized water to form a mixture of glyoxal concentration of 190g / L, potassium permanganate concentration of 55g / L of the second intermediate solution; according to the volume ratio of the first intermediate solution to the second intermediate solution of 5: 2 ratio of the second intermediate solution was added to the first intermediate solution, mixed to form a substitute solution;
[0107] b2. Immerse the intermediate A in the replacement liquid (the weight of the intermediate A immersed in each liter of the replacement liquid is 290 g), react for 2 hours at room temperature to obtain copper foam with an organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) formed on the surface, denoted as intermediate B.
[0108] Step [3] Load manganese-magnesium-gadolinium oxide Mn 1-x Mg x Gd2O4 (0 < x ≤ 0.3) nanocrystals, specifically including the following operations:
[0109] c1. Add magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxybutanedioic acid to deionized water to form an intermediate product formation liquid with a magnesium chloride concentration of 50 g / L, a manganese nitrate concentration of 145 g / L, a gadolinium nitrate concentration of 246 g / L, an allyl alcohol concentration of 75 mL / L, and a 2-hydroxybutanedioic acid concentration of 130 g / L. Immerse the intermediate B in the intermediate product formation liquid (the weight of the intermediate B immersed in each liter of the intermediate product formation liquid is 245 g), place it in a microwave reactor, microwave heat it to 120 °C at a rate of 20 °C / min, and react for 1.2 hours to load the manganese-magnesium-gadolinium oxide intermediate product on the organic compound layer of maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) on the surface of the copper foam matrix, and finally obtain intermediate C;
[0110] c2. Place the intermediate C in a low-temperature box furnace and keep it at 210 °C for 4 hours to convert the manganese-magnesium-gadolinium oxide intermediate product into manganese-magnesium-gadolinium oxide nanocrystals, and finally obtain the sewage oxidation treatment material (copper foam-based maleamide / trimethylamine oxide iron Fe(C4H3NO2)2(C3H9NO) organic matter loaded with manganese-magnesium-gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals).
[0111] The above are only the preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and its core idea of the present invention, and is not used to limit the protection scope of the present invention. Any modifications, equivalent replacements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sewage oxidation treatment material based on magnetocaloric effect, characterized in that: It contains the following steps in order: Step [1] Forming trimethylamine iron oxide Fe(C3H9NO) on the surface of the copper foam substrate 3 The organic compound layer includes the following operations: a1. The carbonyl iron powder, ferric chloride, diethylamine and acetic acid were added to deionized water and mixed to form a base liquid; methyl formate was added to methanol and mixed to form an additive liquid; a certain amount of the additive liquid was added to the base liquid and mixed to form a synthetic liquid; a2. Immerse the copper foam sample in the synthetic solution, heat to 60-90°C, react for 4-6 hours, and obtain trimethylamine iron oxide Fe(C3H9NO) formed on the surface. 3 The copper foam of the organic compound layer is denoted as intermediate A; Step [2] Oxidation of trimethylamine iron Fe(C3H9NO) by substitution of maleimide group C4H3NO2 3 The organic compound layer is converted into a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer, specifically including the following operations: b1. N-methylaniline and phenylhydrazine were added to ethanol and mixed to form a first intermediate solution; glyoxal and potassium permanganate were added to deionized water and mixed to form a second intermediate solution; a certain amount of the second intermediate solution was added to the first intermediate solution and mixed to form a replacement solution; b2. The intermediate A is immersed in the replacement solution and reacted at room temperature for 1.5-3 hours to obtain a copper foam having a maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer formed on the surface, recorded as intermediate B; Step [3] Load manganese-magnesium-gadolinium oxide Mn 1-x Mg x Gd2O4 nanocrystals, where 0 < x ≤ 0.3, specifically including the following operations: c1. Magnesium chloride, manganese nitrate, gadolinium nitrate, allyl alcohol and 2-hydroxysuccinic acid are added to deionized water to form an intermediate product forming liquid, intermediate B is immersed in the intermediate product forming liquid, placed in a microwave reactor, and microwave heated to 90°C-140°C at a rate of 10-30°C / min, and reacted for 0.5-2 hours to load manganese magnesium gadolinium oxide intermediate product on the maleamide / trimethylamine iron oxide Fe(C4H3NO2)2(C3H9NO) organic compound layer on the surface of the foam copper substrate, and finally obtain intermediate C; c2. placing the intermediate C into a low temperature box furnace and keeping it at 150°C-300°C for 3-5 hours to convert the manganese magnesium gadolinium oxide intermediate into manganese magnesium gadolinium oxide nanocrystals, and finally obtaining the wastewater oxidation treatment material.
2. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step a1, the concentration of carbonyl iron powder in the base liquid is 160g / L-220g / L, the concentration of ferric chloride is 50g / L-90g / L, the concentration of diethylamine is 90mL / L-160 mL / L, and the concentration of acetic acid is 90mL / L-140 mL / L; the concentration of methyl formate in the additive liquid is 110mL / L-130 mL / L; and the volume ratio between the additive liquid and the base liquid in the synthetic liquid is 1~3:3~5.
3. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step a2, the weight of the foamed copper immersed in each liter of the synthetic solution is 260-290 g.
4. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step b1, the concentration of N-methylaniline in the first intermediate solution is 160 mL / L-190 mL / L, and the concentration of phenylhydrazine is 210 mL / L-240 mL / L; the concentration of glyoxal in the second intermediate solution is 150 g / L-210 g / L, and the concentration of potassium permanganate is 40 g / L-70 g / L; the volume ratio between the first intermediate solution and the second intermediate solution in the replacement solution is 3-7:1-2.
5. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step b2, the weight of the intermediate A immersed in each liter of the replacement liquid is 270-310 g.
6. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step c1, the intermediate product forming liquid has a magnesium chloride concentration of 40 g / L-60 g / L, a manganese nitrate concentration of 120 g / L-170 g / L, a gadolinium nitrate concentration of 230 g / L-270 g / L, an allyl alcohol concentration of 60 mL / L-90 mL / L, and a 2-hydroxysuccinic acid concentration of 110 g / L-150 g / L.
7. The method for preparing a sewage oxidation treatment material based on magnetocaloric effect according to claim 1, characterized in that: In step c1, the weight of the intermediate B immersed in each liter of the intermediate product forming liquid is 220-270 g.
Citation Information
Patent Citations
Preparation method and application of alternating magnetic field-oriented auxiliary photo-Fenton catalyst
CN116726943A
Method for producing oxide-based metal-organic framework materials by inserting oxides while controlling water content
WO2011069541A1